2021
DOI: 10.1158/0008-5472.can-20-2297
|View full text |Cite
|
Sign up to set email alerts
|

NPM–ALK-Induced Reprogramming of Mature TCR-Stimulated T Cells Results in Dedifferentiation and Malignant Transformation

Abstract: Fusion genes including NPM–ALK can promote T-cell transformation, but the signals required to drive a healthy T cell to become malignant remain undefined. In this study, we introduce NPM–ALK into primary human T cells and demonstrate induction of the epithelial-to-mesenchymal transition (EMT) program, attenuation of most T-cell effector programs, reemergence of an immature epigenomic profile, and dynamic regulation of c-Myc, E2F, and PI3K/mTOR signaling pathways early during transformation. A mutant of NPM–ALK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Pawlicki et al. have recently demonstrated that the reprogramming induced by NPM-ALK is central for T cell transformation and full acquisition of a neoplastic phenotype ( 26 ). However, in contrast to other TCR related molecules, such as CD3, LCK or ZAP70, CD45 is only downregulated and not completely repressed because altered levels of CD45 can affect T cell development within the thymus and T cell survival in the periphery ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pawlicki et al. have recently demonstrated that the reprogramming induced by NPM-ALK is central for T cell transformation and full acquisition of a neoplastic phenotype ( 26 ). However, in contrast to other TCR related molecules, such as CD3, LCK or ZAP70, CD45 is only downregulated and not completely repressed because altered levels of CD45 can affect T cell development within the thymus and T cell survival in the periphery ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the CD45RO isoform was affected by NPM-ALK, whereas the CD45RA isoform was not, as observed by flow cytometry and western blot analyses (Figure 2B and Supplementary Figures 1A, B). We and others previously reported that ALK oncogenic activity controls protein expression through transcriptional regulation or epigenetic silencing (6,25,26). We then investigated the mechanisms of ALK regulation on CD45 expression in ALCL cell lines.…”
Section: Genementioning
confidence: 97%
“…A total of 2 × 10 6 T cells were cultured in 2 mL R10 media in 12-well plates and replated in fresh R10 media every 3 to 4 d for 28 d. At each medium change, cells were maintained at a concentration of 1 × 10 6 cells/mL and counted using the Countess 3 FL Automated Cell Counter (Invitrogen) using Trypan blue (Gibco) as a viability stain. NPM–ALK-transduced T cells were used as a positive control for transformed T cells and have been described previously ( 34 , 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of ALK+ ALCL tumor cells have been shown to express at least one T-cell specific marker. This pleiotropic combination of markers observed in ALK+ ALCL has rendered the identification of the cell of origin difficult, with reports proposing either a thymic or a peripheral origin [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo approaches in mice have failed to phenocopy human ALK+ ALCL and rather often yield B-cell lymphomas [ 12 16 ]. More recently, transduction of primary human CD4+ T lymphocytes with the NPM-ALK transgene has led to in vitro transformation of the cells [ 7 , 8 , 17 ] and in vivo tumor formation [ 7 , 17 ]. However, lentiviral expression does not precisely reproduce gene dosage nor the spatiotemporal variations in gene expression associated with the various stages of differentiation.…”
Section: Introductionmentioning
confidence: 99%